The Viscosity of Aqueous Suspensions of Cellulose Fibers: Part 1. Influence of Consistency and Fiber Length - Silveira,Maria Teresa (2002)
The viscosity of aqueous suspensions of cellulose fibres from eucalyptus and pine bleached kraft pulps has been measured as a function of consistency and fibre length. Empirical correlations have been established between the viscosity of the suspensions and the above mentioned properties.